Comparative Evaluation of Canal Transportation and Centering Ratio in Curved Canals: A Study of Cone-beam Computed Tomography and Micro-computed Tomography - Shantiaee , Yazdan; Zandi , Babak; Rahbar Taramsari , Ali; Akbarzadeh Baghban , Alireza; Zargar, Nazanin; Shojaeian , Shiva; Mortezapour , Niloofar; Shantiaee , Kourosh; Soltaninejad, Fatemeh (Iranian Endodontic Journal, 2023)
Introduction: This study aimed to compare the accuracy and agreement between cone-beam computed tomography (CBCT) and micro-computed tomography (micro-CT) in the assessment of canal transportation and centering ratio following root canal instrumentation with rotary files. Material and Methods: Twenty mesiobuccal canals of mandibular molars were prepared using the 2Shape sequential rotary system. CBCT and micro-CT scans were performed before and after instrumentation, and the magnitude of transportation and centering ratio were measured. The acceptable transportation was set at ≤0.15 mm. The accuracy and agreement between CBCT and micro-CT were calculated, and the intra-class correlation coefficient (ICC) and kappa coefficient were determined to assess the agreement between the two modalities. Statistical analyses were performed using repeated measures ANOVA. Results: Transportation was detected by both modalities at all distances from the apex after instrumentation. The agreement between CBCT and micro-CT in assessing canal transportation was observed in 80%, 85%, 75%, and 75% of specimens at 1-, 3-, 5-, and 7-mm from the apex, respectively. The ICC for transportation and centering ratio was much lower than 0.75, indicating poor agreement between the modalities. The kappa coefficient did not show acceptable agreement between the methods. Conclusions: CBCT and micro-CT demonstrated poor agreement in assessing canal transportation and centering ratio. Micro-CT remains the preferred modality for in vitro investigations, while CBCT should be limited to clinical settings.